Implementation of various data encryption methods for medical information transmission - Neelima, S; Brinda, R (International Journal of Engineering and Technology, 2018)
Encryption is the process of converting the data from readable format into unreadable format with help of any mathematical expression or sometimes with the help of key. On the other hand decryption is the reverse process of encryption with help of same key used at encryption or with the help of some other key. The paper presents the different methodology used for encryption and decryption. Several methods presented in the literature are reviewed. The methods- Rivest-Shamir-Adlemen algorithm, Data Encryption Standard, Advanced Encryption Standard and three different Secure Hash Algorithm are reviewed and implemented using various FPGA devices. The power consumption, delay and area are analyzed and compared. From the analyses it is been found that the performance of AES and SHA3 are better when compared to other algorithms. These algorithms provide high security when compared to rest of the methods.Â Â